A modified high-nickel ternary material, a preparation method thereof, and a battery containing the same
Patent Information
- Application Number
- CN202611165736.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-27
AI Technical Summary
然而,高镍三元正极材料的商业化应用面临着诸多瓶颈
本发明提供的改性高镍三元材料中通过特定的钨元素对高镍三元基体进行体相掺杂并采取特定的钛酸锂进行包覆,二者协同作用,一方面可以利用W6+掺杂可以拓宽Li+迁移通道,同时Li2TiO3包覆层可以进一步为Li+界面迁移提供快速通道,二者配合可以显著降低电荷转移阻力和界面阻抗;另一方面,W6+掺杂可以形成高键能的W-O键,从而显著强化晶格框架,抑制充放电过程中的H2-H3不可逆相转变、晶格体积变化和微裂纹产生,同时Li2TiO3包覆层可以进一步有效隔离正极与电解液,抑制HF腐蚀和过渡金属离子溶解,进一步改善体积变化和微裂纹的恶化问题;由此,特定体相掺杂与表面包覆相结合的协同改性策略,可以实现高镍三元正极材料结构和界面的双重协同优化,进而有效改善其循环稳定性、倍率性能和高温性能,为高能量密度锂离子电池正极材料的开发提供有效途径。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery technology and relates to a modified high-nickel ternary material, its preparation method, and a battery containing it. Background Technology
[0002] With the rapid development of new energy vehicles and large-scale energy storage, the market has placed higher demands on the energy density, cycle life, and rate performance of lithium-ion batteries. High-nickel cathode materials, due to their advantages of high specific capacity, relatively low cost, and moderate voltage platform, have become core candidate materials for high-energy-density lithium-ion batteries. However, the commercial application of high-nickel ternary cathode materials faces numerous bottlenecks. For example, during cycling, issues such as cation mixing, irreversible phase transitions, electrolyte decomposition, and lattice oxygen release occur, causing anisotropic volume expansion of primary particles and leading to microcracks in secondary particles. This increases the contact area between the cathode material and the electrolyte, exacerbating harmful side reactions. This not only causes rapid capacity decay and decreased cycle stability but may also induce thermal runaway and other safety hazards, severely hindering its commercialization process. Summary of the Invention
[0003] In view of the problems existing in the prior art, the purpose of this invention is to provide a modified high-nickel ternary material, its preparation method, and a battery containing the same. The modified high-nickel ternary material includes a core and a coating layer; the core includes a tungsten-doped high-nickel ternary matrix, and the coating layer includes lithium titanate. This invention utilizes W through bulk tungsten doping. 6+ Ion-enhanced lattice framework, broadened Li + Migration channels, combined with the surface Li2TiO3 interface layer coating, can stabilize the cathode / electrolyte interface, inhibit HF corrosion and transition metal ion dissolution, thereby achieving a dual improvement in the structural stability and interface stability of the cathode material, effectively improving its cycle stability, rate performance and high-temperature performance.
[0004] To achieve this objective, the present invention adopts the following technical solution: In a first aspect, the present invention provides a modified high-nickel ternary material, comprising a core and a coating layer covering the core; the core comprises a tungsten-doped high-nickel ternary matrix; in the high-nickel ternary matrix, the molar amount of nickel accounts for 80% or more of the total molar amount of nickel, cobalt and manganese; the coating layer comprises lithium titanate.
[0005] To address the problems of poor structural stability, severe interfacial side reactions, and poor high-temperature performance in existing high-nickel ternary cathode materials, this invention provides a modified high-nickel ternary material in which a specific tungsten element is used for bulk doping of the high-nickel ternary matrix, followed by coating with a specific lithium titanate. The synergistic effect of these two processes, on the one hand... 6+ Doping can broaden the Li +Migration channels, and the Li2TiO3 coating can further facilitate the migration of Li. + Interface migration provides a fast path, and the combination of the two can significantly reduce charge transfer resistance and interface impedance; on the other hand, W 6+ Doping can form high-bond-energy WO bonds, thereby significantly strengthening the crystal lattice framework and suppressing irreversible H2-H3 phase transformation, lattice volume changes, and microcrack formation during charge and discharge. At the same time, the Li2TiO3 coating layer can further effectively isolate the cathode from the electrolyte, suppress HF corrosion and transition metal ion dissolution, and further improve the problems of volume changes and microcrack deterioration. Thus, the synergistic modification strategy of combining specific bulk phase doping with surface coating can achieve dual synergistic optimization of the structure and interface of high-nickel ternary cathode materials, thereby effectively improving their cycle stability, rate performance, and high-temperature performance, providing an effective way for the development of high-energy-density lithium-ion battery cathode materials.
[0006] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. The technical objectives and beneficial effects of the present invention can be better achieved and realized through the following technical solutions.
[0007] As a preferred embodiment of the present invention, the doping amount of tungsten accounts for 0.1% to 0.8% of the molar amount of the high-nickel ternary matrix in the core. For example, it can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, or 0.8%, etc., preferably 0.2% to 0.5%. That is, the chemical formula of the tungsten-doped high-nickel ternary matrix can be written as Li(Ni) x Co y Mn 1-x-y ) 1-z W z O2, where x ≥ 0.8, for example, it can be 0.8, 0.85, 0.88, 0.90, 0.92, 0.96 or 0.98, etc.; y ≤ 0.2, for example, it can be 0.2, 0.15, 0.12, 0.1, 0.08, 0.04 or 0.02, etc.; z = 0.002~0.008, for example, it can be 0.002, 0.003, 0.004, 0.005, 0.006, 0.007 or 0.008, etc.
[0008] In this invention, W 6+ Insufficient doping concentration prevents the formation of a continuous WO network in the bulk phase, hindering the effective suppression of the irreversible H2-H3 phase transition. It also reduces lithium-ion channels, preventing effective connection with the fast ion channels formed by lithium titanate coating. 6+ The ionic radius is relatively large. When the doping amount is too high, it is easy for segregation to occur at the grain boundary or surface, which can easily form an inert second phase, resulting in a significant increase in interfacial impedance.
[0009] As a preferred embodiment of the present invention, the coating layer has a coating amount of 0.5% to 2% of the mass of the core. For example, it can be 0.5%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, or 2.0%, etc.
[0010] In this invention, if the coating amount of lithium titanate is too small, the coating layer cannot form a continuous and dense coverage, and the active sites on the positive electrode surface are exposed to the electrolyte, which cannot effectively inhibit the dissolution of transition metals. In addition, the discontinuous coating will also affect the continuous lithium-ion channel from the electrolyte to the bulk phase. Since the ionic conductivity of lithium titanate is lower than that of high-nickel ternary materials, if the coating amount is too high, it will hinder the lithium-ion transport rate.
[0011] In a second aspect, the present invention provides a method for preparing the modified high-nickel ternary material described in the first aspect, the method comprising: A high-nickel ternary hydroxide precursor, a first lithium source, and a tungsten source are mixed and ground to obtain a mixed powder. First, the mixed powder is pre-calcined at a first temperature under a first oxygen-containing atmosphere. Then, the oxygen content is increased and the temperature is increased. The powder is then calcined at a second temperature under a second oxygen-containing atmosphere to obtain a tungsten-doped high-nickel ternary matrix. The tungsten-doped high-nickel ternary matrix, the second lithium source, and the titanium source are mixed in a dispersant to prepare a sol-gel precursor solution, which is then evaporated to dryness to obtain a dry gel-coated powder. The powder coated with the dry gel is sintered to form a coating layer, thereby obtaining a modified high-nickel ternary material.
[0012] The preparation method described in this invention uses a sol-gel method, which allows Li₂TiO₃ to be uniformly coated on the surface of the matrix particles and facilitates the formation of a good interfacial bond. This ensures the optimized effect of the coating layer, making it both insulating against the electrolyte and protecting the Li₂TiO₃. + Interface transmission.
[0013] As a preferred embodiment of the present invention, the chemical formula of the high-nickel ternary hydroxide precursor is Ni x Co y Mn 1-x-y (OH)2, where x≥0.8, for example, it can be 0.8, 0.85, 0.88, 0.90, 0.92, 0.96 or 0.98, etc.; y≤0.2, for example, it can be 0.2, 0.15, 0.12, 0.1, 0.08, 0.04 or 0.02, etc.
[0014] Preferably, the tungsten source comprises tungsten trioxide (WO3). Preferably, the purity is ≥99.9%. In this invention, tungsten trioxide is preferably used as a dopant material because of its moderate reactivity and the fact that its decomposition does not introduce other impurities or gases, which is beneficial for the subsequent coating of lithium titanate.
[0015] Preferably, the first lithium source comprises lithium hydroxide (LiOH·H2O). Preferably, the molar amount of lithium in the first lithium source is 1.03 to 1.08 times that of the high-nickel ternary hydroxide precursor. For example, it can be 1.03 times, 1.04 times, 1.05 times, 1.06 times, 1.07 times, or 1.08 times, etc.
[0016] Preferably, the amount of raw material used is controlled according to the doping amount of tungsten as a percentage of the molar amount of the theoretically generated high-nickel ternary matrix. For example, it can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, or 0.8%, etc.
[0017] Preferably, the mixing and grinding method includes ball milling, with a ball milling speed of 100 rpm to 600 rpm, such as 100 rpm, 200 rpm, 300 rpm, 400 rpm, 500 rpm, or 600 rpm; and a time of 2 h to 6 h, such as 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h, or 6 h.
[0018] As a preferred embodiment of the present invention, the volume percentage of oxygen in the first oxygen-containing atmosphere is 15% to 35%. For example, the oxygen content can be 15%, 18%, 20%, 23%, 25%, 28%, 30%, 32%, or 35%, etc. The first oxygen-containing atmosphere is preferably air.
[0019] Preferably, the first temperature is 450℃~500℃; the pre-calcination time is 4h~6h. For example, the temperature can be 450℃, 460℃, 480℃, 490℃ or 500℃, etc.; the time can be 4h, 4.3h, 4.5h, 4.8h, 5.0h, 5.3h, 5.5h, 5.8h or 6.0h, etc.; the heating rate can be 1℃ / min~8℃ / min, for example, 1℃ / min, 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min, 6℃ / min, 7℃ / min or 8℃ / min, etc.
[0020] Pre-calcination is preferred in this invention. Its main purpose is to promote the diffusion of W into the lattice of the precursor, form high bond energy WO bonds, strengthen the lattice, and further, pre-calcination can initially decompose the residual lithium compounds on the surface, which can provide a cleaner and more uniform adhesion interface for the subsequent LiTiO3 coating layer.
[0021] As a preferred embodiment of the present invention, the volume percentage of oxygen in the second oxygen-containing atmosphere is 80% to 100%. For example, the oxygen content can be 80%, 82%, 83%, 85%, 88%, 90%, 92%, 95%, 98%, or 100%. The second oxygen-containing atmosphere is preferably pure oxygen.
[0022] Preferably, the second temperature is 700℃~800℃; the pre-calcination time is 12h~18h. For example, the temperature can be 700℃, 730℃, 750℃, 780℃ or 800℃, etc.; the time can be 12h, 14h, 15h, 16h, 17h or 18h, etc.; the heating rate can be 1℃ / min~5℃ / min, for example, 1℃ / min, 2℃ / min, 3℃ / min, 4℃ / min or 5℃ / min, etc.
[0023] As a preferred embodiment of the present invention, the second lithium source includes lithium nitrate.
[0024] Preferably, the titanium source comprises tetrabutyl titanate. Preferably, the molar ratio of lithium in the second lithium source to titanium in the titanium source is 2:1.
[0025] Preferably, the dispersant comprises ethanol.
[0026] Preferably, the titanium source and the second lithium source are first mixed in a dispersant to obtain a sol precursor, and then a tungsten-doped high-nickel ternary matrix is added, mixed, and then evaporated.
[0027] Preferably, when using tetrabutyl titanate as a titanium source for mixing, the dropping rate is controlled to be 1 drop / second to 3 drops / second, and continuous stirring is performed during the dropping process to prevent local hydrolysis.
[0028] Preferably, the amount of raw material used is controlled according to the theoretically generated lithium titanate mass being 0.5% to 2% of the mass of the tungsten-doped high-nickel ternary matrix. For example, it can be 0.5%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, or 2%, etc.
[0029] Preferably, in the sol precursor, the molar concentration of titanium in the titanium source is 0.5 mol / L to 1 mol / L. For example, it can be 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, or 1.0 mol / L, etc.
[0030] As a preferred embodiment of the present invention, the evaporation method includes water bath heating, wherein the water bath heating temperature is 60℃~90℃, and the stirring speed is 100rpm~800rpm. For example, the temperature can be 60℃, 65℃, 70℃, 75℃, 80℃, 85℃, or 90℃, etc.; for example, the stirring speed can be 100rpm, 200rpm, 300rpm, 400rpm, 500rpm, 600rpm, 700rpm, or 800rpm, etc.
[0031] As a preferred embodiment of the present invention, the sintering is carried out in an air atmosphere at a temperature of 650℃~700℃ for 3h~6h. For example, the temperature can be 650℃, 660℃, 670℃, 680℃, 690℃, or 700℃, etc.; the time can be 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, or 6h, etc.
[0032] Preferably, after sintering, the material is naturally cooled to room temperature and then ground to obtain the modified high-nickel ternary material.
[0033] Thirdly, the present invention provides a battery comprising the modified high-nickel ternary material described in the first aspect, or the modified high-nickel ternary material obtained by the preparation method described in the second aspect.
[0034] It should be noted that, due to space limitations and to avoid redundancy, this invention does not exhaustively list all point values within the above numerical range, but it is not limited to the listed values either; other unlisted values within the above numerical range are also applicable.
[0035] Compared with existing technical solutions, the present invention has at least the following beneficial effects: The modified high-nickel ternary material provided by this invention involves bulk doping of the high-nickel ternary matrix with a specific tungsten element and coating with a specific lithium titanate. The two work synergistically, allowing for the utilization of W... 6+ Doping can broaden the Li + Migration channels, while the Li2TiO3 coating can further enhance the Li... + Interface migration provides a fast path, and the combination of the two can significantly reduce charge transfer resistance and interface impedance; on the other hand, W 6+Doping can form high-bond-energy WO bonds, thereby significantly strengthening the crystal lattice framework and suppressing irreversible H2-H3 phase transformation, lattice volume changes, and microcrack formation during charge and discharge. At the same time, the Li2TiO3 coating layer can further effectively isolate the cathode from the electrolyte, suppress HF corrosion and transition metal ion dissolution, and further improve the problems of volume changes and microcrack deterioration. Thus, the synergistic modification strategy of combining specific bulk phase doping with surface coating can achieve dual synergistic optimization of the structure and interface of high-nickel ternary cathode materials, thereby effectively improving their cycle stability, rate performance, and high-temperature performance, providing an effective way for the development of high-energy-density lithium-ion battery cathode materials. Detailed Implementation
[0036] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention.
[0037] The scope of this invention can be defined by lower and upper limits. The selected lower and upper limits define the boundaries of a specific range. The range defined in this way can be defined by the inclusion or exclusion of endpoints. Any endpoint can be independently selected for inclusion or exclusion, and all lower and upper limits can be arbitrarily combined to form new ranges. That is, any lower limit can be combined with any upper limit to form an effective range. For example, if the ranges of 60~120 and 80~110 are listed for specific parameters, it should be understood that the ranges of 60~110 and 80~120 also fall within the scope of this invention. In addition, if the minimum range values 1 and 2 are listed, and the maximum range values 3, 4 and 5 are also listed, then all ranges of 1~3, 1~4, 1~5, 2~3, 2~4 and 2~5 fall within the scope of this invention. In this invention, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range "0~5" means that all real numbers between 0 and 5 have been fully listed in this document, and "0~5" is only a shortened representation of this set of numerical combinations. When a parameter is expressed as an integer ≥2, it is equivalent to listing positive integers that meet the requirements, such as 2, 3, 4, 5, 6, 7, 8, 9, 10, etc. When a parameter is expressed as an integer selected from "2~10", it is equivalent to listing any integer among 2, 3, 4, 5, 6, 7, 8, 9, and 10.
[0038] In this invention, "a combination of at least two" refers to a quantity greater than or equal to 2 unless otherwise specified. For example, "any one or a combination of at least two" means that any one of the listed items can be selected, or a combination of at least two of the listed items formed in a manner that does not conflict and enables the implementation of this invention. In this invention, unless otherwise specified, the features or solutions corresponding to "and / or" cover any one of two or more related listed items, as well as any and all combinations of the related listed items. The arbitrary and all combinations include any two related listed items, any more related listed items, or a combination of all related listed items. For example, "A and / or B" means a set consisting of A, B, and combinations of A and B, where "containing A and / or B" can be understood, depending on the context of the statement, as containing A, containing B, or simultaneously containing both A and B. In this invention, "optional" means that the corresponding feature, component, step or solution is not necessary, that is, it is selected from either "with" or "without". If there are multiple "optional" limitations in a technical solution, unless otherwise specified and there is no technical conflict or mutual constraint, each "optional" limitation is independent and does not affect the others.
[0039] In this invention, technical features or solutions described using open-ended terms such as "comprising" or "including" do not exclude additional non-conflicting elements beyond the listed elements unless otherwise specified. They are considered to disclose both closed-ended features or solutions consisting solely of the listed elements and open-ended features or solutions that may include additional non-conflicting elements beyond the listed elements. For example, if A includes a1, a2, and a3, unless otherwise specified, this means that A can consist only of a1, a2, and a3, or it can include other non-conflicting elements based on a1, a2, and a3. This corresponds to the disclosure of technical solutions such as "A consists of a1, a2, and a3," "A is selected from a1, a2, and a3," and "A not only includes a1, a2, and a3, but may also include other non-conflicting elements." All embodiments and optional embodiments of this invention, unless otherwise specified and without technical conflict, can be combined to form new technical solutions, and such combinations fall within the scope of this invention. The term "embodiment" as used in this invention means that a specific feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment or implementation of the invention. The appearance of this phrase in various locations throughout the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment mutually exclusive with other embodiments. Those skilled in the art will understand, explicitly and implicitly, that the embodiments described in this invention can be combined with other embodiments that do not conflict with the technology. The ordinal numbers "first," "second," "third," and "fourth," etc., used in the expressions "first aspect," "second aspect," "third aspect," and "fourth aspect" in this invention are for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor should they be construed as implicitly specifying the importance or quantity of the indicated technical features. They serve only as a non-exhaustive enumeration and do not constitute a closed limitation on quantity.
[0040] In this invention, the order in which the steps are written in the methods described in the various embodiments does not imply a strict execution order. The actual execution order of each step should be determined based on its function and possible internal logic. Unless otherwise specified, all steps of this invention can be executed in the order they are written, or in any order without technical conflict. For example, if the method includes steps (a) and (b), it means that the method may include steps (a) and (b) executed sequentially, or it may include steps (b) and (a) executed sequentially. If the method also includes step (c), then step (c) can be added to the method in any conflict-free order, including but not limited to the execution order of steps (a), (b), and (c), steps (a), (c), and (b), steps (c), (a), and (b), etc.
[0041] Example 1 This embodiment provides a modified high-nickel ternary material, consisting of a core and a coating layer covering the core; the core is a tungsten-doped high-nickel ternary matrix with the chemical formula Li(Ni) 0.9 Co 0.05 Mn 0.05 ) 0.995 W 0.005 O2, i.e., the doping amount of tungsten in the high-nickel ternary matrix LiNi in the core. 0.9 Co 0.05 Mn 0.05 The molar amount of O2 is 0.5%; the coating layer is lithium titanate, and the coating amount of the coating layer is 1% of the mass of the core.
[0042] The preparation method of this modified high-nickel ternary material includes the following steps: Step S1: Ni 0.9 Co 0.05 Mn 0.05 (OH)2, the first lithium source LiOH·H2O and the tungsten source WO3 (purity ≥99.9%) were mixed in a molar ratio of 1:1.05:0.005, and anhydrous ethanol was used as the ball milling medium with a ball-to-material ratio of 4:1. The mixture was ball milled in a ball mill at a speed of 300 rpm for 4 hours to obtain a uniform mixed powder. Step S2: First, the mixed powder is pre-calcined at 480°C for 5 hours in air at a heating rate of 4°C / min; then, it is calcined at 750°C for 15 hours in pure oxygen at a heating rate of 3°C / min. After naturally cooling to room temperature, it is ground through a 200-mesh sieve to obtain a high-nickel ternary matrix doped with tungsten. Step S3: Weigh out the second lithium source LiNO3, the titanium source tetrabutyl titanate (lithium to titanium molar ratio 2:1), and water ethanol without dispersant, according to the Li2TiO3 coating amount being 1% of the tungsten-doped high-nickel ternary matrix powder. Mix them together. The dropping rate of the titanium source is controlled at 2 drops per second. During the dropping process, stir continuously and magnetically stir until completely dissolved to obtain the sol precursor solution. The total concentration of titanium source in the sol precursor solution is 0.8 mol / L. Step S4: Add the tungsten-doped high-nickel ternary matrix to the above sol precursor solution and mix. Stir at 400 rpm in a water bath at 80°C until the solvent is completely evaporated to obtain a dry gel-coated powder. Step S5: The dry gel-coated powder is heated to 650°C in air at a heating rate of 4°C / min and sintered for 5 hours. After naturally cooling to room temperature, it is ground to obtain the modified high-nickel ternary material.
[0043] Example 2 This embodiment provides a modified high-nickel ternary material, consisting of a core and a coating layer covering the core; the core is a tungsten-doped high-nickel ternary matrix with the chemical formula Li(Ni) 0.9 Co 0.05 Mn 0.05 ) 0.998 W 0.002 O2, i.e., the doping amount of tungsten in the high-nickel ternary matrix LiNi in the core. 0.9 Co 0.05 Mn 0.05 The molar amount of O2 is 0.2%; the coating layer is lithium titanate, and the coating amount of the coating layer is 0.5% of the mass of the core.
[0044] The preparation method of this modified high-nickel ternary material includes the following steps: Step S1: Ni 0.9 Co 0.05 Mn 0.05 (OH)2, the first lithium source LiOH·H2O and the tungsten source WO3 (purity ≥99.9%) are mixed in a molar ratio of 1:1.05:0.002, and anhydrous ethanol is used as the ball milling medium with a ball-to-material ratio of 4:1. The mixture is ball milled in a ball mill at a speed of 500 rpm for 2.5 h to obtain a uniform mixed powder. Step S2: First, the mixed powder is pre-calcined at 450°C for 4 hours in air at a heating rate of 4°C / min; then, it is calcined at 700°C for 12 hours in pure oxygen at a heating rate of 5°C / min. After naturally cooling to room temperature, it is ground through a 200-mesh sieve to obtain a high-nickel ternary matrix doped with tungsten. Step S3: Weigh out the second lithium source LiNO3, the titanium source tetrabutyl titanate (lithium to titanium molar ratio 2:1), and water ethanol without dispersant, according to the Li2TiO3 coating amount of 0.5% of the high nickel ternary matrix powder doped with tungsten element. Mix them with the titanium source at a dropping rate of 2 drops per second. Stir continuously during the dropping process and stir magnetically until completely dissolved to obtain the sol precursor solution. The total concentration of titanium source in the sol precursor solution is 0.5 mol / L. Step S4: Add the tungsten-doped high-nickel ternary matrix to the above sol precursor solution and mix. Stir at 400 rpm in a water bath at 80°C until the solvent is completely evaporated to obtain a dry gel-coated powder. Step S5: The dry gel-coated powder is heated to 670°C in air at a heating rate of 3°C / min and sintered for 3 hours. After naturally cooling to room temperature, it is ground to obtain the modified high-nickel ternary material.
[0045] Example 3 This embodiment provides a modified high-nickel ternary material, consisting of a core and a coating layer covering the core; the core is a tungsten-doped high-nickel ternary matrix with the chemical formula Li(Ni) 0.9 Co 0.05 Mn 0.05 ) 0.992 W 0.008 O2, i.e., the doping amount of tungsten in the high-nickel ternary matrix LiNi in the core. 0.9 Co 0.05 Mn 0.05 The molar amount of O2 is 0.8%; the coating layer is lithium titanate, and the coating amount of the coating layer is 2.0% of the mass of the core.
[0046] The preparation method of this modified high-nickel ternary material includes the following steps: Step S1: Ni 0.9 Co 0.05 Mn 0.05 (OH)2, the first lithium source LiOH·H2O and the tungsten source WO3 (purity ≥99.9%) were mixed in a molar ratio of 1:1.05:0.008, and anhydrous ethanol was used as the ball milling medium with a ball-to-material ratio of 4:1. The mixture was ball milled in a ball mill at a speed of 400 rpm for 3 hours to obtain a uniform mixed powder. Step S2: First, the mixed powder is pre-calcined at 500°C for 6 hours in air at a heating rate of 6°C / min; then, it is calcined at 780°C for 18 hours in pure oxygen at a heating rate of 5°C / min. After naturally cooling to room temperature, it is ground through a 200-mesh sieve to obtain a high-nickel ternary matrix doped with tungsten. Step S3: Based on the Li2TiO3 coating amount being 2% of the tungsten-doped high-nickel ternary matrix powder, weigh out the second lithium source LiNO3, titanium source tetrabutyl titanate (lithium to titanium molar ratio 2:1), and water-ethanol without dispersant, mix them, control the dropping rate of titanium source to 2 drops per second, and continuously stir during the dropping process. After magnetic stirring until completely dissolved, a sol precursor solution is obtained, and the total concentration of titanium source in the sol precursor solution is 1.0 mol / L; Step S4: Add the tungsten-doped high-nickel ternary matrix to the above sol precursor solution and mix. Stir at 400 rpm in a water bath at 80°C until the solvent is completely evaporated to obtain a dry gel-coated powder. Step S5: The dry gel-coated powder is heated to 700°C in air at a heating rate of 2°C / min and sintered for 6 hours. After naturally cooling to room temperature, it is ground to obtain the modified high-nickel ternary material.
[0047] Example 4 The difference between this embodiment and Embodiment 1 is that the amount of tungsten source used in step S1 is adjusted so that the doping amount of tungsten element is adjusted from the proportion of the high-nickel ternary matrix LiNi in the core. 0.9 Co 0.05 Mn 0.05 The molar amount of O2 was adjusted from 0.5% to 0.1%, and all other conditions were exactly the same as in Example 1.
[0048] Example 5 The difference between this embodiment and Embodiment 1 is that the amount of tungsten source used in step S1 is adjusted so that the doping amount of tungsten element is adjusted from the proportion of the high-nickel ternary matrix LiNi in the core. 0.9 Co 0.05 Mn 0.05 The molar amount of O2 was adjusted from 0.5% to 0.25%, and all other conditions were exactly the same as in Example 1.
[0049] Example 6 The difference between this embodiment and Embodiment 1 is that the amount of tungsten source used in step S1 is adjusted so that the doping amount of tungsten element is adjusted from the proportion of the high-nickel ternary matrix LiNi in the core. 0.9 Co 0.05 Mn 0.05 The molar amount of O2 was adjusted from 0.5% to 0.8%, and all other conditions were exactly the same as in Example 1.
[0050] Example 7 The difference between this embodiment and Embodiment 1 is that in step S3, the amount of the second lithium source and the titanium source tetrabutyl titanate is adjusted so that the coating amount of lithium titanate is adjusted from 1% of the mass of the core to 0.2%. Apart from the above, the other conditions are exactly the same as in Embodiment 1.
[0051] Example 8 The difference between this embodiment and Embodiment 1 is that in step S3, the amount of the second lithium source and the titanium source tetrabutyl titanate is adjusted so that the coating amount of lithium titanate is adjusted from 1% of the mass of the core to 0.5%. Apart from the above, the other conditions are exactly the same as in Embodiment 1.
[0052] Example 9 The difference between this embodiment and Embodiment 1 is that the amount of the second lithium source and the titanium source tetrabutyl titanate is adjusted in step S3, so that the coating amount of lithium titanate is adjusted from 1% of the mass of the core to 2.0%. Apart from the above, the other conditions are exactly the same as in Embodiment 1.
[0053] Example 10 The difference between this embodiment and Embodiment 1 is that in step S3, the amount of the second lithium source and the titanium source tetrabutyl titanate is adjusted so that the coating amount of lithium titanate is adjusted from 1% of the mass of the core to 3.0%. Apart from the above, the other conditions are exactly the same as in Embodiment 1.
[0054] Comparative Example 1 The difference from Example 1 is that a high-nickel ternary matrix LiNi is used. 0.9 Co 0.05 Mn 0.05 O2 was used for subsequent testing without modification. Except for the above, all other conditions were exactly the same as in Example 1.
[0055] Comparative Example 2 The difference from Example 1 is that a high-nickel ternary matrix Li(Ni) doped with tungsten is used. 0.9 Co 0.05 Mn 0.05 ) 0.992 W 0.008 O2 was used for subsequent testing without further coating. Except for the above, all other conditions were exactly the same as in Example 1.
[0056] Comparative Example 3 The difference from Example 1 is that a high-nickel ternary matrix LiNi is used. 0.9 Co 0.05 Mn 0.05 O2 is used as the core, and it is not doped, but lithium titanate is coated according to the method of Example 1. Except for the above, the other conditions are exactly the same as those in Example 1.
[0057] Comparative Example 4 The difference from Example 1 is that the tungsten source used for doping is replaced with aluminum source alumina. Apart from the above, the other conditions are exactly the same as in Example 1.
[0058] Comparative Example 5 The difference from Example 1 is that the tungsten source used for doping is replaced with a second titanium source, titanium dioxide. Apart from the above, the other conditions are exactly the same as in Example 1.
[0059] Comparative Example 6 The difference from Example 1 is that the coating layer is replaced with LATP (lithium aluminum titanium phosphate) instead of lithium titanate, and the raw materials used for coating in step S3 are replaced with lithium nitrate, aluminum nitrate nonahydrate, tetrabutyl titanate, ammonium dihydrogen phosphate, complexing agent citric acid, and crosslinking agent diethanol. A sol precursor solution is formed by stirring in water and anhydrous ethanol at 120°C. Except for the above, the other conditions are exactly the same as in Example 1.
[0060] Characterization and Testing The materials obtained in the examples and comparative examples were used as positive electrode materials, and CR2025 coin-type button cells were assembled. The entire process was carried out in an argon-protected glove box with water and oxygen content both <0.1ppm, as detailed below: First, prepare the working electrode (positive electrode sheet). Mix the target positive electrode material, conductive carbon black and PVDF at a mass ratio of 93:3.5:3.5. Add NMP and adjust the liquid-solid ratio to 1:1.4 to form a viscous slurry. Coat the slurry onto the aluminum foil current collector using a doctor blade coating method. First, heat the slurry in a vacuum oven at 50℃ for 8 hours to remove the solvent. Then, heat the slurry to 120℃ for 10 hours to remove residual NMP. After cooling, cut the slurry into a circular sheet with a diameter of 13mm for later use. The battery is then assembled, with the positive electrode (active material side up), polypropylene / polyethylene composite porous membrane, and appropriate amount of electrolyte (1 mol·L⁻¹) added sequentially. -1 LiPF6 is dissolved in a solution with a volume ratio of DMC / EC / EMC of 1:1:1. The lithium metal negative electrode sheet, gasket, and spring are placed inside the CR2025 positive electrode shell. The negative electrode shell is then covered and pressed flat. After removing the glove box, the glove box is sealed with a sealing machine to complete the assembly. After assembly, the battery was tested at room temperature in constant current charge-discharge mode using a LAND battery tester (CT 2001A). The voltage window was set to 2.8~4.3V or 2.8~4.2V. The initial charge-discharge was at 0.1C (1.0C = 200 mA·g). -1 After activating the cells by cycling 3 times, long-cycle tests can be performed by cycling 200 times at 1.0C or 100 times at 1C, depending on the requirements. Alternatively, the rate performance stability can be examined by cycling 5 times at 0.3C, 0.5C, 1C, 1.5C, 2C, 5C, and 0.1C respectively. The capacity retention rate and voltage decay trend of each battery are recorded. The results are shown in Table 1 below.
[0061] Table 1 As can be seen from Table 1: As can be seen from Example 1 and Comparative Example 1, if the ternary precursor is not bulk doped and surface coated, it will suffer from the dual degradation of microcrack propagation caused by the severe anisotropic contraction of the internal lattice and electrolyte decomposition during cycling, resulting in a decrease in cycling performance.
[0062] As can be seen from the comparison between Example 1 and Comparative Example 2, if only bulk doping is performed without surface coating, although the crystal lattice can be stabilized and phase transitions can be suppressed, it cannot prevent the electrolyte from eroding the material surface. The interfacial impedance continues to increase, and the capacity retention rate can only reach 81.2%.
[0063] A comparison of Example 1 and Comparative Example 3 shows that if only surface coating is performed without bulk doping, although the electrolyte can be physically isolated, it cannot suppress the loss of lattice oxygen and the increase of microcracks caused by the harmful H2-H3 phase transition inside the bulk phase, resulting in a capacity retention rate of only 78.6%. As can be seen from Example 1 and Comparative Examples 4 and 5, compared to Al and Ti, W 6+ With a high charge, doping produces a larger Coulomb pinning effect and stronger WO bonds, thus more effectively suppressing the severe anisotropic shrinkage of the lattice caused by the harmful H2→H3 phase transition.
[0064] As can be seen from the comparison between Example 1 and Comparative Example 6, the capacity cycle retention rate decreases when LATP (lithium aluminum titanium phosphate) is used to modify and coat the high-nickel ternary cathode material. This may be because an insulating impurity phase is generated during calcination at 650°C, which increases impedance and reduces the lithium-ion transport rate. Compared with other fast-ion conductors, lithium titanate has higher chemical stability and mechanical strength. In this invention, the coating layer can better synergize with the bulk tungsten doping.
[0065] A comparison of Example 1 and Examples 4-6 shows that, with W 6+ With increasing doping concentration, the cycle capacity initially increases and then decreases. When the doping concentration is insufficient, W... 6+ It cannot form a continuous stabilizing effect within the crystal lattice. Its suppression of the H2-H3 phase transition and mitigation of microcracks are limited. When the doping concentration is too high, W... 6+ Segregation occurs at grain boundaries, forming resistive secondary phases that hinder lithium-ion transport channels, leading to a decrease in capacity. A comparison of Examples 1 and 7-10 shows that as the Li₂TiO₃ coating amount increases, the cycle capacity initially increases and then decreases. A thin coating layer is insufficient to form a complete and uniform protective layer on the particle surface. Exposed surfaces are still susceptible to electrolyte erosion, resulting in limited performance improvement. An excessively thick coating layer forms a barrier, hindering lithium-ion transport.
[0066] As shown in Table 1, the modified high-nickel ternary material provided in this embodiment of the invention effectively overcomes the limitations of a single modification method through the synergistic effect of specific tungsten doping and lithium titanate coating: utilizing W 6+ Doping can effectively suppress harmful phase transitions during charging and discharging, improve lattice stability, and broaden the crystal structure of Li. + Migration channels effectively enhance ion conduction rates and optimize rate performance; further, the use of Li₂TiO₃ coating allows for the formation of a good interfacial bond on the particle surface, facilitating the flow of Li₂TiO₃. + Interface migration has been further enhanced to provide a fast track, ensuring Li +On the one hand, it can effectively isolate the electrolyte, inhibit HF corrosion and transition metal ion dissolution, effectively improve the chemical stability of the coating, reduce the corrosion of the positive electrode by the electrolyte, and reduce the deterioration of irreversible phase transition, volume change and microcracks in the positive electrode material; through the synergistic effect of the two, the cycle capacity retention rate and cycle stability can be greatly improved with a small capacity loss.
[0067] The preferred embodiments of the present invention have been described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solution of the present invention, and these simple modifications all fall within the protection scope of the present invention.
[0068] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not describe the various possible combinations separately.
[0069] Furthermore, various different embodiments of the present invention can be combined in any way, as long as they do not violate the spirit of the present invention, they should also be regarded as the content disclosed by the present invention.
Claims
1. A modified high-nickel ternary material, characterized in that, It includes a core and a coating layer covering the core; the core includes a high-nickel ternary matrix doped with tungsten; in the high-nickel ternary matrix, the molar amount of nickel accounts for 80% or more of the total molar amount of nickel, cobalt and manganese; the coating layer includes lithium titanate.
2. The modified high-nickel ternary material according to claim 1, characterized in that, The tungsten doping amount accounts for 0.1% to 0.8% of the molar amount of the high-nickel ternary matrix in the core; Preferably, the coating layer has a coating amount of 0.5% to 2% of the mass of the core.
3. A method for preparing the modified high-nickel ternary material according to claim 1 or 2, characterized in that, The preparation method includes: A high-nickel ternary hydroxide precursor, a first lithium source, and a tungsten source are mixed and ground to obtain a mixed powder. First, the mixed powder is pre-calcined at a first temperature under a first oxygen-containing atmosphere. Then, the oxygen content is increased and the temperature is increased. The powder is then calcined at a second temperature under a second oxygen-containing atmosphere to obtain a tungsten-doped high-nickel ternary matrix. The tungsten-doped high-nickel ternary matrix, the second lithium source, and the titanium source are mixed in a dispersant to prepare a sol-gel precursor solution, which is then evaporated to dryness to obtain a dry gel-coated powder. The powder coated with the dry gel is sintered to form a coating layer, thereby obtaining a modified high-nickel ternary material.
4. The method for preparing the modified high-nickel ternary material according to claim 3, characterized in that, The tungsten source includes tungsten trioxide; Preferably, the first lithium source comprises lithium hydroxide; Preferably, the amount of raw materials used is controlled according to the doping amount of tungsten element being 0.1% to 0.8% of the molar amount of the theoretically generated high-nickel ternary matrix.
5. The method for preparing the modified high-nickel ternary material according to claim 3 or 4, characterized in that, The oxygen content in the first oxygen-containing atmosphere is 15% to 35% by volume; the first oxygen-containing atmosphere is preferably air. Preferably, the first temperature is 450℃~500℃; the pre-calcination time is 4h~6h.
6. The method for preparing the modified high-nickel ternary material according to any one of claims 3-5, characterized in that, The volume percentage of oxygen in the second oxygen-containing atmosphere is 80% to 100%; the second oxygen-containing atmosphere is preferably pure oxygen. Preferably, the second temperature is 700℃~800℃; the pre-calcination time is 12h~18h.
7. The method for preparing the modified high-nickel ternary material according to any one of claims 3-6, characterized in that, The second lithium source includes lithium nitrate; Preferably, the titanium source comprises tetrabutyl titanate; Preferably, the dispersant comprises ethanol; Preferably, the amount of raw materials used is controlled according to the principle that the mass of theoretically generated lithium titanate accounts for 0.5% to 2% of the mass of the tungsten-doped high-nickel ternary matrix; Preferably, in the sol precursor, the molar concentration of titanium in the titanium source is 0.5 mol / L to 1 mol / L.
8. The method for preparing the modified high-nickel ternary material according to any one of claims 3-7, characterized in that, The method of evaporation includes water bath heating, wherein the temperature of the water bath heating is 60℃~90℃ and the stirring speed is 100rpm~800rpm.
9. The method for preparing the modified high-nickel ternary material according to any one of claims 3-8, characterized in that, The sintering is carried out in an air atmosphere at a temperature of 650℃~700℃ for 3h~6h. Preferably, after sintering, the material is naturally cooled to room temperature and then ground to obtain the modified high-nickel ternary material.
10. A battery, characterized in that, The material contains the modified high-nickel ternary material as described in claim 1 or 2, or the modified high-nickel ternary material obtained by the preparation method described in any one of claims 3-9.